Selective separation of lambdacyhalothrin by porous/magnetic molecularly imprinted polymers prepared by Pickering emulsion polymerization. Issue 19 (27th August 2013) - Hang, Hui; Li, Chunxiang; Pan, Jianming; Li, Linzi; Dai, Jiangdong; Dai, Xiaohui; Yu, Ping; Feng, Yonghai
<x xml:space="preserve">Abstract</x> Porous/magnetic molecularly imprinted polymers (PM‐MIPs) were prepared by Pickering emulsion polymerization. The reaction was carried out in an oil/water emulsion using magnetic halloysite nanotubes as the stabilizer instead of a toxic surfactant. In the oil phase, the imprinting process was conducted by radical polymerization of functional and cross‐linked monomers, and porogen chloroform generated steam under the high reaction temperature, which resulted in some pores decorated with easily accessible molecular binding sites within the as‐made PM‐MIPs. The characterization demonstrated that the PM‐MIPs were porous and magnetic inorganic–polymer composite microparticles with magnetic sensitivity (Ms = 0.7448 emu/g), thermal stability (below 473 K) and magnetic stability (over the pH range of 2.0–8.0). The PM‐MIPs were used as a sorbent for the selective binding of lambdacyhalothrin (LC) and rapidly separated under an external magnetic field. The Freundlich isotherm model gave a good fit to the experimental data. The adsorption kinetics of the PM‐MIPs was well described by pseudo‐second‐order kinetics, indicating that the chemical process could be the rate‐limiting step in the adsorption of LC. The selective recognition experiments exhibited the outstanding selective adsorption effect of the PM‐MIPs for target LC. Moreover, the PM‐MIPs regeneration without significant loss in adsorption capacity was demonstrated by at least four repeated cycles.